Early Arterial Embolization and Mortality in Mechanically Ventilated Patients With Hemoptysis: A Nationwide Retrospective Cohort Study. Issue 10 (October 2020) - Ando, Takahiro; Kawashima, Masahiro; Jo, Taisuke; Masuda, Kimihiko; Yamauchi, Yasuhiro; Tanaka, Goh; Kage, Hidenori; Suzukawa, Maho; Nagai, Hideaki; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo; et al.
Abstract : Objectives: Hemoptysis, a symptom common across various respiratory diseases, can cause airway obstruction leading to a life-threatening condition. Arterial embolization has been used to control bleeding from the lower airways. However, limited studies have evaluated its effects on in-hospital mortality in patients with hemoptysis requiring mechanical ventilation. The objective of this study was to clarify whether early intervention by arterial embolization reduced mortality in mechanically ventilated patients with hemoptysis. Design: Retrospective cohort study from July 2010 to March 2017. Setting: More than 1, 200 acute-care hospitals, comprising approximately 90% of all tertiary-care emergency hospitals in Japan. Patients: The study cohort was patients with pulmonary diseases hospitalized for hemoptysis and mechanically ventilated within 2 days of admission. Interventions: We compared patients who had undergone arterial embolization within 3 days of endotracheal intubation (early embolization group) with patients who did not (control group). Measurements and Main Results: A total of 12, 287 patients with hemoptysis requiring mechanical ventilation were analyzed. After 1:4 propensity score matching, there were 226 and 904 patients in the early embolization and control groups, respectively. The early embolization group was associated with lower 7-day and 30-day mortalities (7-d mortality: 1.3% vs 4.0%; odds ratio, 0.39; 95% CI, 0.16–0.97; p = 0.044 and 30-d mortality: 7.5% vs 16.8%; odds ratio, 0.45; 95% CI, 0.28–0.73; p = 0.001) and shorter duration of mechanical ventilation (median 6 d, interquartile range 4–13 d vs 8 d, interquartile range 4–19 d; p = 0.003) compared with the control group. Conclusions: Our results show that early intervention by arterial embolization may be effective in reducing 7-day and 30-day mortalities in patients with life-threatening hemoptysis requiring mechanical ventilation. Abstract : Supplemental Digital Content is available in the text.